Genetic basis of pulmonary arterial hypertension: a prospective study from a highly inbred population. (July 2021) - Aldalaan, Abdullah M.; Ramzan, Khushnooda; Saleemi, Sarfraz A.; Weheba, Ihab; Alquait, Laila; Abdelsayed, Abeer; Alzubi, Fatima; Zaytoun, Hamdeia; Alharbi, Nadeen; Al-Owain, Mohammed; Imtiaz, Faiqa
Pulmonary arterial hypertension (PAH), whether idiopathic PAH (IPAH), heritable PAH, or associated with other conditions, is a rare and potentially lethal disease characterized by progressive vascular changes. To date, there is limited data on the genetic basis of PAH in the Arab region, and none from Saudi Arabian patients. This study aims to identify genetic variations and to evaluate the frequency of risk genes associated to PAH, in Saudi Arabian patients. Adult PAH patients, diagnosed with IPAH and pulmonary veno-occlusive disease, of Saudi Arabian origin, were enrolled in this study. Forty-eight patients were subjected to whole-exome sequencing, with screening of 26 genes suggested to be associated with the disease. The median age at diagnosis was 29.5 years of age, with females accounting for 89.5% of our cohort population. Overall, we identified variations in nine genes previously associated with PAH, in 16 patients. Fourteen of these variants have not been described before. Plausible deleterious variants in risk genes were identified in 33.3% (n = 16/48) of our entire cohort and 25% of these cases carried variants in BMPR2 (n = 4/16). Our results highlight the genetic etiology of PAH in Saudi Arabia patients and provides new insights for the genetic diagnosis of familial and IPAH as well as for the identification of the biological pathways of the disease. This will enable the development of new target therapeutic strategies, for a disease with a high rate of morbidity and mortality.